Insights into using green and unconventional technologies to recover natural astaxanthin from microbial biomass - Mussagy, Cassamo U.; Pereira, Jorge F. B.; Santos-Ebinuma, Valéria C. [UNESP]; Pessoa, Adalberto; Raghavan, Vijaya (Taylor & Francis, 2022)
Microorganisms such as bacteria, microalgae and fungi, are natural and rich sources of several valuable bioactive antioxidant’s compounds, including carotenoids. Among the carotenoids with antioxidant properties, astaxanthin can be highlighted due to its pharmaceutical, feed, food, cosmetic and biotechnological applications. The best-known producers of astaxanthin are yeast and microalgae cells that biosynthesize this pigment intracellularly, requiring efficient and sustainable downstream procedures for its recovery. Conventional multi-step procedures usually involve the consumption of large amounts of volatile organic compounds (VOCs), which are regarded as toxic and hazardous chemicals. Considering these environmental issues, this review is focused on revealing the potential of unconventional extraction procedures [viz., Supercritical Fluid Extraction (SFE), Ultrasound-Assisted Extraction (UAE), Microwave-Assisted Extraction (MAE), High-Pressure Homogenization (HPH)] combined with alternative green solvents (biosolvents, eutectic solvents and ionic liquids) for the recovery of microbial-based astaxanthin from microalgae (such as Haematococcus pluvialis) and yeast (such as Phaffia rhodozyma) cells. The principal advances in the area, process bottlenecks, solvent selection and strategies to improve the recovery of microbial astaxanthin are emphasized. The promising recovery yields using these environmentally friendly procedures in lab-scale are good indications and directions for their effective use in biotechnological processes for the production of commercial feed and food ingredients like astaxanthin.
Keywords: astaxanthin; Carotenoids; green solvents; unconventional extraction procedures